A Descriptive Study to Assess the Knowledge of School Teachers Regarding School Health Programme in Selected Rural Schools of Waghodia - Belagavi, Dayanand; E.V. , Nirmal Raj; P. Joseph, Rajesh; Yesvekar, Honey; Chaudhari, Rohit; Rathva, Bhavisha (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Education is the backbone of development, and in order to be really fit for school, children need to be healthy. Those who suffer from health cannot concentrate or actively participate in school. Healthy children, on the other hand, attend school more regularly and can benefit fully from what the education system has to offer. Hence, school health programs have the greater potential to link resources for education, health, nutrition, and sanitation for school teachers and children at school. Material and methods: A descriptive research design was conducted to assess the knowledge regarding the school health program among 60 school teachers of selected rural primary and secondary schools of Waghodia by the purposive sampling technique. A self-structured knowledge questionnaire was used to assess the knowledge. Descriptive analysis was done by using Excel and SPSS 20. Results: More than half of 36 (60%) school teachers had poor knowledge regarding the school health program, and 24 (40%) of school teachers had average but none of them were at the level of very poor or good knowledge. In relation to the area-wise school health programme shows that the overall mean percentage of the knowledge scores was 44.43% with a mean and SD of 13.33±2.297. The current study reveals that there was no significant association between mean knowledge score and age, gender, qualification, religion, marital status, family type, working area, and experience of school teachers, 0.05). Conclusion: School teachers had an average knowledge of the school health program, which implies greater effort to be made by improving their awareness of the various school health programs periodically. Moreover, the teachers’ experience may affect the understanding of the health programs.